2022
DOI: 10.3390/fi14030069
|View full text |Cite
|
Sign up to set email alerts
|

Transformer-Based Abstractive Summarization for Reddit and Twitter: Single Posts vs. Comment Pools in Three Languages

Abstract: Abstractive summarization is a technique that allows for extracting condensed meanings from long texts, with a variety of potential practical applications. Nonetheless, today’s abstractive summarization research is limited to testing the models on various types of data, which brings only marginal improvements and does not lead to massive practical employment of the method. In particular, abstractive summarization is not used for social media research, where it would be very useful for opinion and topic mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It is important to emphasize that, in the field of social media summarization, few research works [7,8,9] have demonstrated transformer-based social media abstractive text summarization systems. Our system aims to optimize the results achieved so far in two main points.…”
Section: Importance Of Social Media Summarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that, in the field of social media summarization, few research works [7,8,9] have demonstrated transformer-based social media abstractive text summarization systems. Our system aims to optimize the results achieved so far in two main points.…”
Section: Importance Of Social Media Summarizationmentioning
confidence: 99%
“…A Transformer-based abstractive summarization is presented in [7] which creates summaries in three languages from posts and comment pools. The datasets are from Reddit and Twitter.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…In carrying out text summary tasks there are many techniques that can be used, one of which is using the most popular models such as the Transformer-based Text-to-Text Transfer Transformer or the T5 model which has advantages in producing good text summaries. However, several studies conducted by Mastropaolo et al [21], Fendji et al [22], and Blekanov et al [23] revealed that the T5 model still has room to improve performance in the process of carrying out text summary tasks, this study will use Bayesian optimization techniques that will perform a task in increasing the performance of the T5 model. In the Bayesian optimization task, we will use Bayesian probability theory for an iterative model so that it can have the advantage of updating initial knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Everyday communication similar to that described in [12] tends to create communitiesan element of communication architecture with dynamic composition, blurred borders, thresholds to enter, and internal "center-periphery" structure [13]. Detecting communities within socially mediated discussions helps to rethink the structure of social grouping as well as its reasons.…”
mentioning
confidence: 99%
“…Trying to answer the questions posed above, the papers link the phenomena of media, psychological, or social-grouping nature to platform affordances, hierarchies of communicators, geographical proximity of communication loci, or dynamics of seemingly structureless opinion cumulation [11]. Thus, [12] demonstrates, among others, that large-scale international discussions on social networks, such as Twitter, have a certain logic in how their news-like content changes into discussion on problematic issues with varying speeds, depending on the distance from the geographical epicenter of the discussed event. With predominantly methodological goals, the authors fine-tune and test several neural-networkbased models for abstractive summarization, but they also show how summarization applied to real-world online debates allows for discovering their news/issues structure from a comparative perspective.…”
mentioning
confidence: 99%